Business Development Strategies For Batik Panembahan SMEs in Pekalongan Using SWOT Analysis and The Business Model Canvas - Nayla Safarah; Fatimah; Muhamad Subagiyo; Muhammad Nurul Majid (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This study examines the business development strategy of Batik Panembahan, a small and medium enterprise (SME) engaged in the production and sale of micro-fabric batik shirts, which still relies on a market follower approach without distinctive product differentiation. The purpose of this study is to formulate an appropriate business development strategy by integrating SWOT analysis and the Business Model Canvas (BMC). Methods: This research uses a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The research subject is the owner of Batik Panembahan, located in South Pekalongan. Key Findings: The results indicate that the business has strengths in production independence and local distribution networks through Shopee and resellers. However, the main weaknesses include limited capital, the absence of a strong brand image, and suboptimal digital marketing strategies. The Business Model Canvas analysis shows that elements such as customer segments, value propositions, and channels are functioning well, while key partnerships, business legality, and digital management have not been optimally developed. Contribution: This study contributes to the development of SME strategic management by providing an integrated SWOT–BMC model for batik SMEs. Conclusion: Batik Panembahan needs to strengthen product identity, optimize digital marketing, and develop strategic partnerships to enhance competitiveness and achieve sustainable business growth in the creative industry.